A Manganese-Superoxide Dismutase From Thermus thermophilus HB27 Suppresses Inflammatory Responses and Alleviates Experimentally Induced Colitis. Issue 10 (8th May 2019) - Sheng, Yang; Li, Hailong; Liu, Minjun; Xie, Bingxian; Wei, Wen; Wu, Jiawei; Meng, Fanguo; Wang, Hong Yu; Chen, Shuai
Abstract: Background: Superoxide dismutase (SOD) is an attractive therapeutic agent to ameliorate oxidative stress that is critical for the initiation and progression of inflammatory bowel disease (IBD). However, the short life of SOD limits its clinical application. In this study, we aim to examine the therapeutic effects of a hyperthermostable SOD from the Thermus thermophilus HB27 (TtSOD) for treatment of experimentally induced IBD. Methods: A recombinant TtSOD was expressed and purified from Escherichia coli, and its therapeutic effects were examined in 2 experimental IBD animal models. Results: In IBD induced by 2, 4, 6-trinitrobenzenesulfonic acid in zebrafish, TtSOD treatment decreased intestinal enlargement and attenuated neutrophil infiltration, resulting in alleviation of enterocolitis. In mice, SOD activity was substantially increased in the intestine after oral gavage of TtSOD, which ameliorated gut inflammation, preserved gut barrier function, and attenuated the severity of dextran sulfate sodium–induced colitis. Furthermore, TtSOD inhibited lipopolysaccharide-induced production of reactive oxygen species and inflammatory responses in mouse bone marrow–derived macrophages. Conclusions: Our results demonstrate that TtSOD possesses therapeutic activities toward experimentally induced IBD, offering new clinical treatment options for patients with IBD. Abstract : A hyperthermostable SOD from the Thermus thermophilus HB27 (TtSOD) alleviated experimentally-induced colitis in animal models. TtSOD exerted its therapeutic effects at least in part through decreasing reactive oxygen species in macrophages and thereby ameliorating inflammatory responses.